2016
DOI: 10.1002/cbm.1994
|View full text |Cite
|
Sign up to set email alerts
|

Psychologically informed practice (PIP) for staff working with offenders with personality disorder: A pragmatic exploratory trial in approved premises

Abstract: Psychologically informed practice appears to be sufficiently advantageous for staff and offenders, and the trial feasible, which is a full-scale multi-centre trial, seems warranted. Copyright © 2016 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 8 publications
0
15
0
Order By: Relevance
“…Evaluations of the core community service have shown that offender managers value their training in managing complex behaviour, rates of recall are reduced and compliance of offenders can be increased. In addition, research has shown that better understanding of offenders through psychological formulation has led to offenders accessing services where previously they were at an impasse (Brown et al, ; Bruce et al, ; Clark and Chuan, ; Minoudis et al, 2012a, 2012b, 2013). These studies are small, do not have robust control groups and ultimately do not measure the two main outcomes of reduced reoffending and improved psychological well‐being.…”
Section: Evaluating the Pathwaymentioning
confidence: 99%
“…Evaluations of the core community service have shown that offender managers value their training in managing complex behaviour, rates of recall are reduced and compliance of offenders can be increased. In addition, research has shown that better understanding of offenders through psychological formulation has led to offenders accessing services where previously they were at an impasse (Brown et al, ; Bruce et al, ; Clark and Chuan, ; Minoudis et al, 2012a, 2012b, 2013). These studies are small, do not have robust control groups and ultimately do not measure the two main outcomes of reduced reoffending and improved psychological well‐being.…”
Section: Evaluating the Pathwaymentioning
confidence: 99%
“…The modified model, underpinned by the four guiding principles of PIP, comprised; (a) staff training and support; (b) the use of a psychological framework to guide day‐to‐day operations; (c) focus on interpersonal relationships; (d) and evaluation (Bruce et al, 2017). Delivery was in two phases: (a) workforce training; and (b) case consultation and formulation with staff support provided as necessary.…”
Section: Methodsmentioning
confidence: 99%
“…Bruce, Horgan, Kerr, Cullen, and Russell (2017), using a control group, evaluated “Psychologically Informed Practice” (PIP), an innovation designed to assist approved premises' staff. This model encompassed elements of the OPD Community Case Management outlined by Joseph and Benefield (2012) together with the KUF awareness level training (Lamph et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, two related studies have been published that examined the incidence of mental health difficulties in this population and provided an example of specialist service provision for such a group (Hatfield et al, ; Ryan et al, ). More recently, work has been published that provides information about ‘psychologically informed practice’ for APs staff specifically in relation to personality disorder (Bruce et al, ). Whilst these authors suggest that this intervention has an impact, the study has shortcomings, including important differences between the units at the outset, for example, in staff gender ratios or their knowledge about personality disorder at baseline.…”
Section: Introductionmentioning
confidence: 99%